Innovative envirommental technology applications of laser light stimulation - Jakubiak, Mateusz; Gdowska, Katarzyna (Energy and Automation, 2015)
Interdisciplinary studies have pointed out many possible uses of laser biotechnology in environmental engineering and agriculture. A number of previous research studies on the application of low intensity laser stimulation of different biological material proved, that effects of photostimulation may increase biomass production, yield and germination energy. Laser stimulationmay also increase plants resistance to environmental pollutions and unfavorable environmental factors. Methodmay be used also for more efficient sewage treatment process, soil reclamation and increase of bioremediation abilities. Application of laser biotechnology might be use in environmental engineering technologies, according to ideas of sustainable development.